1999
DOI: 10.1007/s11626-999-0115-4
|View full text |Cite
|
Sign up to set email alerts
|

A new human prostate carcinoma cell line, 22Rv1

Abstract: A cell line has been derived from a human prostatic carcinoma xenograft, CWR22R. This represents one of very few available cell lines representative of this disease. The cell line is derived from a xenograft that was serially propagated in mice after castration-induced regression and relapse of the parental, androgen-dependent CWR22 xenograft. Flow cytometric and cytogenetic analysis showed that this cell line represents one hyper DNA-diploid stem line with two clonal, evolved cytogenetic sublines. The basic k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
442
0
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 493 publications
(472 citation statements)
references
References 29 publications
18
442
0
4
Order By: Relevance
“…A lower concentration of gefitinib blocked ligand stimulated EGFR phosphorylation in human keratinocytes, whereas significant inhibition of downstream signaling, that is, MAPK phosphorylation, was achieved only at higher doses of gefitinib. The inhibitory concentrations of gefitinib in NHEK were similar to those observed for blocking pEGFR and pMAPK in 22Rv1 cells (Figure 2B), an androgen-independent prostate cancer cell line (Sramkoski et al, 1999). This confirms previously reported observations of differential inhibition of EGFR and MAPK phosphorylation in glioma cell lines (Li et al, 2003) and shows the effectiveness of gefitinib against EGFR signaling in human keratinocytes.…”
Section: Results Egfr Is the Major Her/erbb Receptor In Primary Humansupporting
confidence: 90%
“…A lower concentration of gefitinib blocked ligand stimulated EGFR phosphorylation in human keratinocytes, whereas significant inhibition of downstream signaling, that is, MAPK phosphorylation, was achieved only at higher doses of gefitinib. The inhibitory concentrations of gefitinib in NHEK were similar to those observed for blocking pEGFR and pMAPK in 22Rv1 cells (Figure 2B), an androgen-independent prostate cancer cell line (Sramkoski et al, 1999). This confirms previously reported observations of differential inhibition of EGFR and MAPK phosphorylation in glioma cell lines (Li et al, 2003) and shows the effectiveness of gefitinib against EGFR signaling in human keratinocytes.…”
Section: Results Egfr Is the Major Her/erbb Receptor In Primary Humansupporting
confidence: 90%
“…In the prostate cell lines examined, expression levels in LNCaP and PC3 cells (derived from prostate metastases; Kaighn et al, 1979;Horoszewicz et al, 1983) were approximately one-fifth those in PNT2C2, P4E6 and 22Rv1 cells (derived from normal prostate cells or primary prostate cancer cells; Berthon et al, 1995;Sramkoski et al, 1999;Maitland et al, 2001). Furthermore, in screens of clonogenic activity with a range of chemotherapeutic agents and UV irradiation, we have found that, in general, PNT2C2 and P4E6 cells show high sensitivity, 22Rv1 cells show intermediate sensitivity and PC3 and LNCaP cells show high resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The CWR22Rv1 cells were derived from a recurrent tumor, following ADT of a CWR22 xenograft, which was originally established from a human prostate primary tumor [47][48][49]. CWR22Rv1 cells are CK5-negative and CK8/18-positive, and express a mutant 114-kDa AR (an in-frame duplication of exon 3 of AR gene, which results in the insertion of 39 amino acids in the DNA-binding domain) [9,43,47].…”
Section: Cwr22rv1 Cellsmentioning
confidence: 99%